2022
DOI: 10.3389/fsufs.2022.873957
|View full text |Cite
|
Sign up to set email alerts
|

Rice Management Decisions Using Process-Based Models With Climate-Smart Indicators

Abstract: Irrigation strategies are keys to fostering sustainable and climate-resilient rice production by increasing efficiency, building resilience and reducing Greenhouse Gas (GHG) emissions. These strategies are aligned with the Climate-Smart Agriculture (CSA) principles, which aim to maximize productivity whilst adapting to and mitigating climate change. Achieve such mitigation, adaptation, and productivity goals- to the extent possible- is described as climate smartness. Measuring climate smartness is challenging,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This irrigation management approach is also documented in the study by Arenas‐Calle et al. (2022). Four cultivars (BRS A702 CL, BRS Catiana, BRS Pampeira, and IRGA 424) were allocated to the subplots.…”
Section: Methodsmentioning
confidence: 58%
See 3 more Smart Citations
“…This irrigation management approach is also documented in the study by Arenas‐Calle et al. (2022). Four cultivars (BRS A702 CL, BRS Catiana, BRS Pampeira, and IRGA 424) were allocated to the subplots.…”
Section: Methodsmentioning
confidence: 58%
“…The cumulative average water application for each irrigation management strategy in the two seasons was 32,436;1,413; 17,039; and 23,104 m 3 ha −1 for CFC, IFA, IFC, and IFF, respectively. This irrigation management approach is also documented in the study by Arenas-Calle et al (2022). Four cultivars (BRS A702 CL, BRS Catiana, BRS Pampeira, and IRGA 424) were allocated to the subplots.…”
Section: Description Of the Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term adoption (i.e., 100 years) is required for sequestration permanence, and net GHG balance can shift over time, even from a sink to a source ( Lugato et al, 2018 ). DNDC has been used in other studies to simulate biogeochemical processes and GHG fluxes in rice-based systems ( Arenas-Calle et al, 2022 ; Babu et al, 2006 ; Zhu et al, 2019 ) and also to characterize nutrient cycling in the rice-wheat systems of India ( Pathak et al, 2006 ). Wang et al (2020) reported a correlation (R) between the observed and simulated CH4 of 0.90 (p < 0.01).…”
Section: Methodsmentioning
confidence: 99%